Reduction in new metastases in breast cancer with adjuvant clodronate treatment - Diel, Ingo J.; Solomayer, Erich-Franz; Costa, Serban-Dan; Gollan, Christina; Goerner, Ronald; Wallwiener, Diethelm; Kaufmann, Manfred; Bastert, Gunther (The New England journal of medicine, 1998)
Bisphosphonates are pyrophosphate analogues that inhibit the formation and dissolution of calcium phosphate crystals in vitro. In vivo, bisphosphonates bind strongly to hydroxyapatite on the bone surface. Used therapeutically, bisphosphonates inhibit osteoclast-mediated bone resorption by mechanisms that are not fully understood.1-3 Clinical trials have demonstrated the anti-osteolytic effect of bisphosphonates in patients with breast cancer and bone metastases. In such patients, bisphosphonates significantly reduced the incidence of hypercalcemia, bone pain, and pathologic fractures, but overall survival was not prolonged.4-6 In experiments in animals, bisphosphonates have been shown to produce a significant reduction in the appearance of new metastases . . .